The Value of Pancasila in Foundation Financial Accountability Practices - Cokorda Gde Bayu Putra; Ni Komang Sumadi; Ni Ketut Muliati (International Journal of Interreligious and Intercultural Studies, 2022)
The main objective of this paper is to explain The Value of Pancasila in Foundation Financial Accountability Practices. Financial accountability is a demand that attempts tonot only ensure that fiancial governance is well effiient, but also to create public trust. The compilation and submission of fiancial reports is one approach of applying fiancialaccountability procedures in a non-profi organization that engages with the public. Through the phenomenological approach, it is found that applications of the teaching of God, Human Value, Spirit of Unity, Spirit of Collaborative, and Justice that constitute Pancasila’s spirit also inspire the Foundation’s spirit of accountability implementation.